Composición del microbioma en suelos con diferentes perfiles edáficos cultivados con Vitis vinifera cv. Malbec - Paolinelli, Marcos; Martinez, Laura Elizabeth; Garcia Lampasona, Sandra Claudia; Díaz Quirós, C.; Farber, Marisa Diana; Escoriaza, Maria Georgina; Longone, Maria Valeria; Sturm, Maria Elena; Chimeno, Selva Valeria; Lerena, María Cecilia; Combina, Mariana; Mercado, Laura Analia (Asociación Argentina de Microbiología (AAM), 2025)
Poster